Thermo-mechanical stresses distribution on bone drilling: numerical and experimental procedures - Fernandes, M.G.A. (2018)
In bone drilling, the temperature and the level of stresses at the bone tissue are function of the drilling parameters. If certain thresholds are exceeded, irreversible damages may occur on the bone tissue. One of the main challenges in the drilling process is to control the associated parameters and even more important, to avoid the surrounding tissue damage. In this study, a dynamic numerical model is developed to determine the thermo-mechanical stresses generated during the bone drilling, using the finite element method. The numerical model incorporates the geometric and dynamic characteristics involved in the drilling processes, as well the developed temperature inside the material.